ANALISIS HUBUNGAN MASLAHAH DAN MAFSADAH DALAM MEMPENGARUHI PEMBENTUKAN HUKUM FIQH PANDEMIK DI MALAYSIA: ANALYSIS OF THE RELATIONSHIP BETWEEN MASLAHAH AND MAFSADAH IN AFFECTING THE FORMATION OF PANDEMIC FIQH RULINGS IN MALAYSIA (International Seminar on Syariah and Law (INSLA), 2020)
Maqasid Syariah is often defined as the ‘objective of Islamic law’, that is, the desired goal behind the obligation of a law.The science of maqasid is very important especially in understanding and interpreting the Islamic texts. Maqasid syariah generally aims topreserve the five basic necessities of human life, namely preserving religion, life, intellect, lineage (as well as dignity) and property.Any effort that supports these five necessities (maslahah) and protects them from harm(mafsadah) is included in thegoals of Islamic law.The concept of maslahahand mafsadahhas always been the main backbonefor the scholarsin determining the law. During the pandemic COVID-19 hitinMalaysia, various legal rulings have been issued by the authorities at the state and federallevelsto protect the affairs of Muslims.The rulingsare issued after consideringthe maslahahand mafsadahto be faced by Muslims in Malaysia. This study was conducted to identify the role of maslahahand mafsadahin influencing the Syariah rulings related to pandemic COVID-19 in Malaysiaas well as showinghow the process takes place(takyīful fiqhī). This study is qualitative, using a library approach to collect primary and secondary data and then analyse it by content analysis.The results show that the principles of maslahahand mafsadahplay a big role in determining the Syariah rulingsin the COVID-19 pandemic situation as well as the need to set a clear standard of maslahahand mafsadahso that the rulings produced are accurate, preciseand not madeitonwhim. Maqasid Syariah seringkali didefinisikan sebagai ‘objektif hukum syarak’, iaitu matlamat yang dikehendaki di sebalik sesuatu hukum itu difardukan. Ilmu maqasid sangat penting khususnya dalam memahami dan menafsirkan nas-nas hukum Syariah. Maqasid syariah secara umumnya bertujuan memelihara lima perkara asas kehidupan manusia iaitu memelihara agama, nyawa, akal, keturunan (serta maruah) dan harta. Mana-mana usaha yang menyokong limaperkara ini (maslahah) dan memeliharanya daripada kerosakan (mafsadah) termasuk di dalam maqasid syarak. Konsep maslahah dan mafsadah sentiasa dijadikan sandaran utama dalam penentuan hukum oleh para ulama. Sepanjang tempoh pandemik COVID-19 melanda Malaysia, pelbagai hukum fiqh telah dikeluarkan oleh pihak berkuasa di peringkat negeri dan persekutuan bagi menjaga hal ehwal umat Islam. Hukum-hakam ini dikeluarkan setelah membuat pertimbangan terhadap maslahah dan mafsadah yang akan dihadapi oleh umat Islam di Malaysia. Kajian ini dijalankan untuk mengenal pasti peranan maslahah danmafsadah dalam mempengaruhi hukum fiqh pandemik COVID-19 di Malaysia selain memperlihatkan bagaimana proses itu berlaku (takyīful fiqhī). Kajian ini bersifat kualitatif, menggunakan pendekatan keperpustakaan mengumpulkan data primer dan sekunder dan seterusnya menganalisanya secara analisis kandungan. Hasil kajian menunjukkan bahawa prinsip maslahah dan mafsadah memainkan peranan yang besar dalam penentuan hukum-hakam fiqh dalam situasi pandemik COVID-19 disamping perlu menetapkan suatu standard maslahah dan mafsadah yang jelas agar hukum yang dihasilkan tepat, jitu dan tidak dibuat sesuka hati.